Pembiusan Monyet Ekor Panjang (Macaca fascicularis) dengan Campuran Ketamine dan Xylazine (THE ANAESTHETIZATION OF LONG TAILED MACAQUE (MACACA FASCICULARIS) BY INJECTING THE COMBINATION OF KETAMINE AND XYLAZINE) - Suartha, I Nyoman; Wandia, I Nengah; Putra, I Gusti Agung Arta; Soma, I Gede; Sudisma, I Gusti Ngurah (Jurnal Veteriner; Vol 2 No 1 (2001), 2016)
Pembiusan Monyet Ekor Panjang ( Macaca fascicularis ) dengan Campuran Ketamine dan Xylazine   (THE ANAESTHETIZATION OF LONG TAILED MACAQUE (MACACA FASCICULARIS) BY INJECTING THE COMBINATION OF KETAMINE AND XYLAZINE)
Keywords: ketamine; xylazine; long tailed macaque; blow-pipe; anaesthesia